Developing of bacterial mutagenic assay system for detection - Baghdad Science Journal (مجلة بغداد للعلوم)
Been Antkhav three isolates of soil classified as follows: Bacillus G3 consists of spores, G12, G27 led Pal NTG treatment to kill part of the cells of the three isolates varying degrees treatment also led to mutations urged resistance to streptomycin and rifampicin and double mutations